Antecedents of Revisit Intention to Pantjoran PIK During Covid-19 Pandemic - Haryono, Joko; Lasut, Flavina M.O; Yulius, Kevin G; Arafah, Willy; Ingkadijaya, Rahmat (Institut Pariwisata dan Bisnis Internasional, 2023)
Revisit intention is a very important factor in the sustainability of a business. This study aims to analyze the factors that influence the revisit intention to Pantjoran PIK, North Jakarta. The exogenous variables in this study were environment, culture, and food safety & hygiene. This research is explanatory research that seeks to explain the relationship between exogenous and endogenous variables. The research instrument used was online questionnaire distributed via Google Form. The research method used is quantitative analysis with individual analysis units and the PLS-SEM approach using SMARTPLS 4 software. Sampling technique used was purposive sampling with 160 samples. The measurement model analysis meets the requirements of convergent validity, reliability and discriminant validity. However, in the structural model analysis, only Food Safety & Hygiene had significant influence on Revisit Intention. These findings are in line with similar research during the Covid-19 pandemic although different sampling technique are suggested with longitudinal data to improve accuracy. Food Court and restaurant owners are suggested to maintain the food safety and hygiene to improve revisit intention during Covid-19 pandemic.